Trust and human resource management - Searle, Rosalind; Skinner, Denise (Cheltenham : Edward Elgar, 2011)
'An organization's human resource management (HRM) policies and their implementation have long been claimed to influence trust within an organizational environment. However there has, until now, been a limited examination of the relationship between the two. In this unique book, the contributors explore the HRM cycle from entry to exit, and examine in detail the issue of trust and its links with HRM. Each chapter takes an aspect of HRM including; selection, performance management, careers and personal development, training, change management and exit, and offers a new understanding and insight into the role, importance and challenges to trust within these processes'--Back cover.
1. Introduction / Rosalind Searle and Denise Skinner -- 2. A Picture of Trust in UK Business Organisations / Les Worrall, Cary L. Cooper and Margaret Lindorff -- 3. The Evolution of Trust and Control as Seen through an Organization's Human Resource Practices / Karen E. Mishra, Gavin M. Schwarz and Aneil K. Mishra -- 4. The Development and Destruction of Organizational Trust During Recruitment and Selection / Rosalind Searle and Jon Billsberry -- 5. Human Resource Management, the Psychological Contract and Trust / David Guest and Mike Clinton -- 6. Human Resource Management, Person-Environment Fit and Trust / Corine Boon and Deanne N. Den Hartog -- 7. Enhancing Trust through Training / Mel Ashleigh and Jane Prichard -- 8. Trusted to Care: Role of Trust in Mentoring / Anthea Wilson and Volker Patent -- 9. Career Development, Progression and Trust /Jonathan R. Crawshaw -- 10. Trust in the Context of Performance Appraisal / Denise Skinner and Rosalind Searle -- 11. Employee Relations and the Illusiveness of Trust / Kim Mather -- 12. Whose Side Are You On? Trust and HR in Workplace Bullying / Susan Harrington and Charlotte Rayner -- 13. When Peers Become Leaders: The Effects of Internal Promotion on Workgroup Dynamics / Susan E. Brodt and Angela M. Dionisi -- 14. Trust and Strategic Change: An Organizational Justice Perspective / Mark N.K. Saunders -- 15. Beyond Attitudes and Norms: Trust Commitment and HR Values as Triggers of Intention to Leave / Shay S. Tzafrir and Guy Enosh -- 16. Trust and Engagement in a Downsizing Context: The Impact on Human Resource Managers / Finian Buckley -- 17. New Agendas and Perspectives / Rosalind Searle and Denise Skinner -- Index.
Includes bibliographical references and index.
Keywords: Personnel management; Trust